2016
DOI: 10.3208/jgssp.ina-02
|View full text |Cite
|
Sign up to set email alerts
|

Assessment to the sediment concentration affected by river water current during dry and monsoon seasons at Kanor village-Bengawan Solo River

Abstract: Sediment transport is the natural phenomenon which is occurred along river stream. Many factors are influencing on this process, but the main parameters are current velocity and flow discharge. The velocity and flow discharge are two river components which intercorrelated each other. Current velocity may cause scouring at the river stream continuously. The materials from scouring process would be become the primary sources of sediment load. There are two sediment load types, suspended load and bed load. The qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The impact of a higher river discharge is presumed to be larger because of the high sediment influx and high erosion potential [13,14]. From Fig.…”
Section: Effect Of River Branches On Sediment Transport Ratementioning
confidence: 99%
“…The impact of a higher river discharge is presumed to be larger because of the high sediment influx and high erosion potential [13,14]. From Fig.…”
Section: Effect Of River Branches On Sediment Transport Ratementioning
confidence: 99%
“…They concluded that sediment load concentrations near the water surface were lower than those at lower levels in the water column, and thus that the sediment load concentration is affected by water depth. Similarly, Maulana et al (2016) considered the difference in the sediment concentration being affected by river water current during the dry and monsoon seasons. They found that there is a linear correlation between sediment concentration and current velocity.…”
Section: Sedimentation In River Channelmentioning
confidence: 99%
“…In Figure 5, it can be seen that the dry unit weight of the sediment increases as the cross-section gets wider and the flow velocity gets lower. Wider sectional area denotes the condition where sediment concentration is high (Maulana et al, 2016;Soemitro et al, 2015). When the sediment concentration is high and the flow velocity is low, conditions favour sediment deposition.…”
Section: Relation Between Properties Of the Sediment And Sampling Locmentioning
confidence: 99%